Kolaborasi Aktor Dalam Pelaksanaan Kebijakan Program Kota Tanpa Kumuh (Kotaku) di Kecamatan Kasemen Kota Serang - Vojana Vojana; Delly Maulana; Rachmi Yulianti (Asosiasi Ilmuwan Administrasi Negara (ASIAN), 2021)
The City Without Slums Program (KOTAKU) is one of the many strategic efforts of the Directorate General of Human Settlements, Ministry of Public Works and Public Housing to assist disaster management in Indonesia and support the “100-0-100 Movement”, namely 100% universal access to drinking water, 0 % collection, and 100% access to proper sanitation. The general objective of this program is to increase access to basic infrastructure and services that are used to support livable, productive, and sustainable use. To achieve achievements in implementing the KOTAKU program, it is necessary to have cooperation or collaboration between the government, the community, and the private sector. Because the role of policy actors greatly determines success in policy formulation, policy implementation considers the consequences of the policies that have been made. Therefore, the purpose of this research is how the collaboration of the actors involved and the role of each actor is. The methodology used in this research is a qualitative method with a descriptive approach carried out through in-depth interviews, observation, and documentation. The results of this study indicate that this program has been implemented optimally, but the results have not been appropriately implemented. The actors who collaborate in the KOTAKU program are DisPERKIM, DPUPR, BAPPEDA, BKM, and the community.